MEMPROGRAMKAN PENGENALAN MANAJEMEN WAKAF DI DESA CIBITUNG TENGAH, KECAMATAN TENJOLAYA, KABUPATEN BOGOR - Rully Trihantana; Bayu Purnama Putra; Basit Tulhuda (Jurnal Pengabdian Kepada Masyarakat Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2023)
This community service aims to program the introduction of waqf management in Central Cibitung Village, Tenjolaya District, Bogor Regency. It is hoped that the introduction of waqf management will help improve the community's economy. The subject of this community service is the people of Central Cibitung Village, Tenjolaya District, Bogor Regency. This activity was carried out using the method of transparency, participation and accountability. The result of this community service is that through productive waqf the community can be assisted in developing their economy, but the managing institution must be good and right in managing the waqf. With this community service, it can be concluded that productive waqf management in the village of Central Cibitung can be reflected through three aspects, namely nazir professionalism, asset management, and financial reporting which has been going well.